Perbandingan Metode Ekstraksi Sokhletasi dan Maserasi Terhadap Aktivitas Antioksidan Ekstrak Daun Ciplukan (Physalis angulata) - Hidayati, Sholihatil (PHARMACON, 2025)
Physalis angulate is a plant that has been used as an antibacterial, anticancer, antiparasitic, anti-inflammatory, antifibrotic and antidiabetic. Ceplukan leaf extract contains the highest total phenolic (equivalent to gallic acid 144.4 mg/g) and total flavonoids (equivalent to quercetin 33.33 mg/g). This study aims to find the best extraction method that can provide optimal antioxidant activity. The research was carried out by collecting ciplukan leaves and drying them to become simplia. Extraction is carried out by maceration and soccreation methods with ethanol solvents. The antioxidant activity test was carried out by the DPPH method using a microplate reader instrument at a wavelength of 517 nm.Data analysis was carried out using linear regression to determine the IC50 value. The results showed that ethanol extract of citrus leaf with extraction method (EECS) showed greater antioxidant activity (IC50 of 202.52±0.90 μg/ml compared to ethanol extract of citrus leaf with maceration extraction method (EECM) with an IC50 value of 328.08±1.48 μg/ml. EECS has good antioxidant activity and can be developed as a health supplement that has properties as an antioxidant.